2012
DOI: 10.1158/1535-7163.mct-12-0248
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Ubiquitin Protease UBP43 as an Antineoplastic Target

Abstract: New pharmacologic targets are needed for lung cancer. One candidate pathway to target is composed of the E1-like ubiquitin-activating enzyme (UBE1L) that associates with interferon-stimulated gene 15 (ISG15), which complexes with and destabilizes cyclin D1. Ubiquitin protease 43 (UBP43/USP18) removes ISG15 from conjugated proteins. This study reports that gain of UBP43 stabilized cyclin D1, but not other D-type cyclins or cyclin E. This depended on UBP43 enzymatic activity; an enzymatically inactive UBP43 did … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 33 publications
6
79
0
Order By: Relevance
“…The PTM ISG15 has distinct functions and is regulated by the DUB USP18 [15,18,35]. Both ISG15 [36] and USP18 [19] are deregulated in different cancers, consistent with an important functional role for this DUB in homeostasis of growth-regulatory proteins. This view is supported by our prior work that established ISGylation affects stability of key growth-regulatory proteins in acute promyelocytic leukemia (APL) and lung cancer [16, 17, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTM ISG15 has distinct functions and is regulated by the DUB USP18 [15,18,35]. Both ISG15 [36] and USP18 [19] are deregulated in different cancers, consistent with an important functional role for this DUB in homeostasis of growth-regulatory proteins. This view is supported by our prior work that established ISGylation affects stability of key growth-regulatory proteins in acute promyelocytic leukemia (APL) and lung cancer [16, 17, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The precise consequences of ISGylation are being elucidated, but there is growing evidence that this pathway has specialized functions [18]. We previously showed that engineered loss of USP18 results in the destabilization of specific oncoproteins [1920 and LM Mustachio personal communication]. Recent work also uncovered a potential tumor suppressive role for USP18 in FVB-Usp18 knockout mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that specific oncogenic proteins including PML/RARα and cyclin D1 were substrates of the ubiquitin-like interferon-stimulated gene 15 (ISG15) modification (ISGylation) pathway (68). This pathway engages the E1 activating enzyme UBE1L, the E2 conjugating enzyme UBCH8 and the E3 ligase that enables ISG15 to bind protein substrates and regulate their stability (911).…”
Section: Introductionmentioning
confidence: 99%
“…The deubiquitinating (DUB) enzyme ubiquitin-specific protease 18 (USP18) is the major enzyme involved in ISG15 removal from substrate proteins (12). USP18 activity reduces ISG15 protein conjugation and promotes tumorigenesis if an oncogenic substrate is stabilized by USP18 (68). USP18 also functions as a negative regulator of interferon (IFN) signaling independent of its ISG15 deconjugase activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…5,9 The thorough dissection of USP18 unraveled its role in antiviral activity and cancer inhibition. [10][11][12] Intriguingly, the gene encoding human USP18 is located on chromosome 22q11.2 in a minimal region deleted in DiGeorge syndrome, which is characterized by immune deficiencies and congenital cardiac abnormalities. 9 Emerging evidence has shed light on the relevance of USP18 to several well-known signaling pathways that participate in cardiac remodeling, including nuclear factor κB, calcineurin-nuclear factor of activated T cells, transforming growth factor-β-activated kinase 1 (TAK1) signaling.…”
mentioning
confidence: 99%